PARADIGMA BARU HADIS: TELAAH PEMIKIRAN M. SYUHUDI ISMAIL - Siregar, Idris (SHAHIH (Jurnal Ilmu Kewahyuan), 2020)
Hadith in Islamic law is the second source after the Qur'an, so important is the position of the hadith so that the hadith also serves as al-Bayan to the law contained in the Qur'an. The textual understanding of classical hadith resulted in the law that was born at that time irrelevant to today's era. To get a correct understanding of the hadiths, the scholars understand the hadiths so that they can answer the challenges of the times. Textual understanding of hadith is not sufficient and irrelevant, so understanding hadith must be contextualized, namely by using social science, anthropology, history and culture. One of the Indonesian hadith scholars M. Syuhudi Ismail, as in his book Textual and Contextual Hadith of the Prophet: A Study of Ma'ani al-Hadith on Universal, Temporal and Local Islamic Teachings. M. Syuhudi Ismail in his book gives an offer in understanding the content of the hadith, namely looking at the shape of the eyes of the hadith and its scope, looking at the background, looking at the content of the hadith, and seeing the clues of hadith that are contradictory. So by looking at these factors then the hadith will be able to answer all the problems that occur in this contemporary era.